Draft Seventh Five Year Plan Andhra Pradesh 1985-90 Volume II Section VIII Education - Planning Commission (Planning Commission, 1985)
General Education As the system of education that existed prior to the Implement of independence was found to be thoroughly defective And was not related to life. culture and aspirations of the Indian People Government of India appointed Commissions and time -to time to achieve the desired objectives. All These Commissions and Committees mode valuable recommendation improving the content and quality of education to be Education ac call levels. The Education Commission 1964 has stressed the enlarged of education in national development. It is rightly assorted that education can be the best instrument of change for national development.
Government of Andhra Pradesh Hyderabad
Finance Planning Department Government of Andhra Pradesh Hyderabad
Keywords: School Education; Higher Education; Adult Education; Registrar of Publication; Jawahar Bal Bhavan; Andhra Pradesh Science Centre; Andhra Pradesh Text Book Press; National Cadet Corps; State Achieves; Public Libraries; Archaeology and Museums; Oriental Manuscripts Library and Research Institute; Cultural Affairs; Andhra Pradesh State Film Development Corporation; Scientific Services and Research